Konsep dasar kebijakan pendidikan - Fadiyah Elwijaya; Vivi Mairina; Nurhizrah Gistituati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2021)
Education policy is important in the process of achieving national education goals so that an understanding of the basic concepts of education policy is needed in order to produce pro-active education policies and problem solving. The purpose of writing this article is to examine the scope of education policy which consists of the meaning of education policy, components of education policy, characteristics of educational policies and implementation of educational policies. This writing methodology uses literature study methodology. The writing of this article was carried out by reviewing 26 journals related to education policy. The results of the study found that education policy is a policy related to the education sector in the process of elaborating the vision and mission of education in order to achieve educational goals through strategic steps in the implementation of education. The education policy component consists of five, namely objectives, plans, programs, decisions, and impacts. The characteristics of education policy are that of having educational objectives, fulfilling legal-formal aspects, having an operational concept, being made by the authorities, being able to be evaluated and having a systematic approach. The approach to implementing educational policy consists of a structural approach, a procedural and managerial approach, a behavioral approach and a political approach.